Clinical Challenges in Pedophilia-Themed Obsessive-Compulsive Disorder - Ferreira, Carla (2021)
In obsessive-compulsive disorder, pedophilia-themed obsessions-distressing intrusive thoughts about being sexually attracted to, or sexually abusing, children-are the most distressing for patients and the most misdiagnosed among healthcare professionals. Our aim is to present a case report highlighting the role stigma plays in delaying treatment, the clinical challenges in the diagnosis, and in the treatment of pedophilia-themed obsessive-compulsive disorder, in order to address the lack of literature on the subject. The case concerns a 33-year-old man with suicidal thoughts associated with the unbearable suffering caused by pedophilia-themed obsessions he had been having over the previous decade, without ever asking for help. This situation was highly disabling, leaving him mostly isolated in his bedroom. After the differential diagnosis was made, a treatment plan combining pharmacological and cognitive-behavioural therapy was implemented. After 18 months he showed a degree of remission that made it possible for him to apply for a job.